Intravenous ω‐3 Fatty Acids Plus Gemcitabine: Potential to Improve Response and Quality of Life in Advanced Pancreatic Cancer. (28th July 2015) - Arshad, Ali; Isherwood, John; Mann, Christopher; Cooke, Jill; Pollard, Cristina; Runau, Franscois; Morgan, Bruno; Steward, William; Metcalfe, Matthew; Dennison, Ashley
Abstract : Background: Marine‐derived ω‐3 fatty acids (ω‐3FAs) have proven antitumor activity in vivo and in vitro and improve quality of life (QOL) in clinical cancer studies. These changes may be mediated by reduction in circulating proangiogenic and proinflammatory factors. In this first study of intravenous ω‐3FAs as a therapy in cancer patients, we aimed to assess if it could augment the antitumor activity of gemcitabine in patients with advanced pancreatic cancer and improve QOL. Materials and Methods: Patients were administered gemcitabine 1000 mg/m 3 weekly followed by up to 100 g (200 mg/mL) of ω‐3 rich lipid emulsion for 3 weeks followed by a rest week. This was continued for up to 6 cycles, progression, unacceptable toxicity, patient request, or death. The primary outcome measure was objective response rate, with secondary outcome measures of overall and progression free survival, QOL scores, and adverse events. Results : Fifty patients were recruited. Response rate was 14.3% and disease control rate was 85.7%. Overall and progression free survival were 5.9 and 4.8 months, respectively. Increase in global health of > 10% over baseline was seen in 47.2% of patients. More than 50% of patients had > 10% increase in QOL scores in generic symptom scores and both disease‐specific domains. Grade 3/4 adverse events were thrombocytopenia (8%), neutropenia (12%), nausea or vomiting (4%), and chills (6%). Conclusion: Intravenous ω‐3FAs in combination with gemcitabine shows evidence of improved activity and benefit to QOL in patients with advanced pancreas cancer and is worthy of investigation in a randomized phase III trial.